Controlling information about creators and their relationships to and across archival records and the law of diminishing returns - Jamison Trivette, Karen (Atlanti, 2024)
Purpose: The purpose of this paper was to consider the archival paradigm respect des fonds and to discuss its challenges over time. The article also covered how the author maintained and demonstrated her respect for this canonical archival prin-ciple through current practice and application with contemporary technology via Access to Memory (AtoM), an online archives management software tool.Methods / Approach: The author conducted qualitative research as she re-viewed the scientific literature as well as the presented work of an expert in the field to ascertain the usefulness of authority records or control as they or it relate to the aforementioned paradigm.Results: The scientific literature revealed just how long ago the challenges to respect des fonds actually began and how they ebbed and flowed over time. The principle’s incorporation into current-day archives management software vehi-cles such as Access to Memory lends to its staying power even in light of the chal-lenges. The author’s literature review revealed ways by which records’ creator authority is established, how such is controlled via historical and more recent approaches, and what values these efforts possess. Conclusions / Findings: Most archival operations are not adequately support-ed. There never seems to be enough resources—time, human, space, budget, and more—to manage everything that requires archivists’ precious attention and skill sets. As such, this author questioned the trend of archival science the-ory leaning evermore towards practices (in this case, the practice of authority control) that drain resources away from mission-critical functions. After inves-tigating this topic, the author found herself with more questions than answers. Where is the line drawn for archivists regarding the delivery of information? In the end, is archival authority control—and the associated tasks which fur-ther exhaust even more of archivists’ meager resources—more a respect des théoriciens than a respect des fonds?
Keywords: archives management systems; authority; authority control; authority record; autorita; avtoriteta; controllo di autorita; creatore di record; normativni nadzor; normativni zapis; provenance; provenienca; provenienza; record di autorita; records creator; sistemi di gestione degli archivi; sistemi za upravljanje arhivov; ustvarjalec dokumentov